Mutu fisik, kimia, dan sensori ikan lemuru (Sardinella sp.) kaleng di PT X, Pengambengan, Bali: Physical, chemical and sensory quality of canned lemuru (Sardinella sp.) during the storage period at PT X, Pengambengan, Bali - Utari, Siluh Putu Sri Dia; Khairunnisa, Anis; Agustin , Novita (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Canning is a method used to prepare and preserve fish by sealing them in airtight containers and sterilizing them. Ensuring uniformity of quality is crucial and continuously supervised to uphold the high standards and food safety of canned fish products. The objective of this study was to assess the stability of chemical properties (pH and histamine), physical properties (viscosity), and sensory quality of canned lemuru fish (Sardinella sp.) in tomato sauce throughout a 12-day storage period. The study included samples of canned lemuru fish from the BTN brand, which is one of the items manufactured by PT X, Pengambengan. These samples were examined in triplicate over a period of 12 weeks to measure pH, histamine levels, viscosity, and sensory attributes such as appearance, texture, taste, scent, and color. Data analysis employed analysis of variance and Duncan's advanced test to determine if there were significant differences at the 5% significance level. The findings indicated that the 12-week observation period had a notable impact (p<0.05) on the acidity level of the tomato sauce medium and the histamine level of the BTN samples. However, the storage duration did not have a significant effect (p>0.05) on the viscosity of the tomato sauce or the sensory quality (appearance, texture, taste, aroma, and color) of the BTN samples. This indicates that the BTN brand-canned lemuru manufactured by PT X demonstrates consistency in terms of the viscosity and sensory attributes of its tomato sauce. However, it lacks consistency in terms of the acidity of the tomato sauce and the level of histamine.